2019
DOI: 10.1002/pros.23772
|View full text |Cite
|
Sign up to set email alerts
|

Zinc promotes prostate cancer cell chemosensitivity to paclitaxel by inhibiting epithelial‐mesenchymal transition and inducing apoptosis

Abstract: Background: Paclitaxel (PTX) is a first-line chemotherapeutic drug for the treatment of prostate cancer. However, most patients develop resistance and metastasis, and thus new therapeutic approaches are urgently required. Recent studies have identified widespread anti-tumor effects of zinc (Zn) in various tumor cell lines, especially prostate cancer cells. In this study, we examined the effects of Zn as an adjuvant to PTX in prostate cancer cells. Methods: PC3 and DU145 cells were treated with different concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 43 publications
1
20
0
Order By: Relevance
“…Previous studies have also shown that the zinc level in hepatoma cells is significantly lower than that in normal liver cells, which is related to the carcinogenesis and progression of HCC [ 59 ]. Zinc released by ZIF-8 degradation may promote the sensitivity of cancer cells to chemotherapeutic drugs and inhibit the development of HCC [ 60 , 61 ]. These may partly explain why the As@ZIF-8 NPs group showed lower IC 50 values and less invasion and migration of residual cells than the ATO group.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also shown that the zinc level in hepatoma cells is significantly lower than that in normal liver cells, which is related to the carcinogenesis and progression of HCC [ 59 ]. Zinc released by ZIF-8 degradation may promote the sensitivity of cancer cells to chemotherapeutic drugs and inhibit the development of HCC [ 60 , 61 ]. These may partly explain why the As@ZIF-8 NPs group showed lower IC 50 values and less invasion and migration of residual cells than the ATO group.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, quercetin was shown to suppress the EMT process, deactivating the PI3K/Akt signaling pathway and downregulating MALAT1, a long noncoding RNA [ 250 ]. Similarly, zinc’s synergistic effect to paclitaxel was demonstrated in PCa cell lines via EMT inhibition by downregulating the expression of TWIST1 [ 251 ].…”
Section: Emt and Therapy Resistance In Prostate Cancermentioning
confidence: 99%
“…Moreover, it causes G2/M arrest 10 . Some reports have indicated that PTX strongly induces cell apoptosis in multiple cancer cells, such as lung cancer cells, 11 breast cancer cells, 12 ovarian cancer cells 13 and PCa cell 14 . However, no report has shown the antitumor effect of NCTD combined with PTX in PCa cells.…”
Section: Introductionmentioning
confidence: 99%